FACTORS CAUSING ATTACK OF WOODEN VESSELS AND MARINE STRUCTURE IN COSTS OF IRAN - Ali Reza nezhad (Regional Information Center for Science and Technology (RICeST), 2002)
Wooden structure, specially vessels and launch boats were studied along all shores and ports of Persian Gulf, Oman Sea and Caspian Sea during two years in different seasons .Factors causing damage in the vessels and coastal wooden constructions were evaluated. Based on the results, north coasts, as compared to south cost of the country, were affected more intensively by fungi damages were lower at Caspian sea shores than those at shores of Persian Gulf and Oman sea. A major reason of this is lower level of salt in Caspian sea than in Persian Gulf. At the south coast, in addition to wood decay, marine borers are the main cause of damages. At coastal zones of Khozestan province, fewer damages were found, as compared to other points of several rivers flowing to the sea at these shores and sailing of vessels through low salt waters.